(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Maintaining affordable and accessible healthcare is a big concern for healthcare institutions. They must change and elevate their performance in order to do this. Organizations must affect employee work performance in order to achieve this. As a result, it’s critical to understand the main aspects of employment stability in the healthcare industry as well as potential improvements. The bulk of research found that factors influencing health workers’ job satisfaction were salary, years of experience, nationality, and marital status. For both male and female nurses, work satisfaction was unaffected by gender or educational attainment. Overall, the study showed some gaps in our understanding of how gender and educational attainment relate to the impact of social determinants of health on the job stability of health workers.